Temperature dependence of the electrical resistivity and absolute thermoelectric power of amorphous metallic glass Ni33.3Zr66.7 - B. Smili; A. Messaoud; W. Bouchelaghem; L. Abadlia; N. Fazel; A. Benmoussa; I. Kaban; F. Gasser; J.G Gasser (Journal des solides non cristallins Volume 481 ,1er février 2018, Pages 352-360, 2018)
Electron transport properties and thermal stability of Ni33.3Zr66.7 metallic glass (MG) have been studied using an original device for simultaneous measurements of electrical resistivity and absolute thermoelectric power (ATP) controlled by a LabView software written by one of us. The electrical resistivity and absolute thermoelectric power were measured simultaneously and very accurately over a temperature range from 25 to 400 °C with a nominal heating rate of 0.5 K min−1. The electronic thermal conductivity was also determined using the Wiedemann–Franz law in the same temperature range. Due to its high efficiency, this technique is more and more used because it is characterized by a high sensitivity to detection of the phase transitions related to electronic transport, which is the aim of this study. Analysis of the temperature dependence of the resistivity and ATP of the Ni33.3Zr66.7 glassy ribbons proves the potential of this characterization method to study the thermal behavior of metallic glasses. The crystal structure and the morphology of Ni33.3Zr66.7 metallic glass in the asquenched state and after heat treatments were studied using X-ray diffraction (XRD), and scanning electron microscope (SEM)
Keywords: Metallic glass Electronic transport properties Electrical resistivity Absolute thermoelectric power Phase transitions Thermal stability